Online adaptive MR-guided radiotherapy: Conformity of contour adaptation for prostate cancer, rectal cancer and lymph node oligometastases among radiation therapists and radiation oncologists. (September 2022) - Rasing, Marnix J.A.; Sikkes, Gonda G.; Vissers, Nicole G.P.M.; Kotte, Alexis N.T.J.; Boudewijn, Joske H.; Doornaert, Patricia A.H.; Eppinga, Wietse S.C.; Intven, Martijn; Rutgers, Reijer H.A.; Scheeren, Annick; Snoeren, Louk M.W.; Vlig, Tiny B.; et al.
Highlights: Contour adaptation conformity analyzed for LN-metastases, rectal- + prostate cancer. Contour adaptation conformity among RTTs and radiation oncologists is comparable. Role expansion of RTTs with daily contour adaptation impacts workflow efficiency. Abstract: Background and purpose: Online adaptive MR-guided treatment planning workflows facilitate daily contour adaptation to the actual anatomy. Allocating contour adaptation to radiation therapists (RTTs) instead of radiation oncologists (ROs) might allow for increasing workflow efficiency. This study investigates conformity of adapted target contours provided by dedicated RTTs and ROs. Materials and methods: In a simulated online procedure, 6 RTTs and 6 ROs recontoured targets and organs at risk (OAR) in prostate cancer (n = 2), rectal cancer (n = 2) and lymph node-oligometastases (n = 2) cases. RTTs gained contouring competence beforehand by following a specific in-house training program. For all target contours and the reference delineations volumetric differences were determined and Dice similarity coefficient (DSC), conformity index (CI) and generalized CI were calculated. Delineation time and –confidence were registered for targets and OAR. Impact of contour adaptation on treatment plan quality was investigated. Results: Delineation conformity was generally high with DSC, CI and generalized CI values in the range of 0.81–0.94, 0.87–0.95 and 0.63–0.85 for prostate cancer, rectal cancer and LN-oligometastasis, respectively. Target volumes were comparable for both, RTTs and ROs. Time needed and confidence in contour adaptation was comparable as well. Treatment plans derived with adapted contours did not violate dose volume constrains as used in clinical routine. Conclusion: After tumor site specific training, daily contour adaptations as needed in adaptive online radiotherapy workflows can be accurately performed by RTTs. Conformity of the derived contours is high and comparable to contours as provided by ROs.